Pharmacological reflection of plants traditionally used to manage diabetes mellitus in Tanzania - Peter, Emanuel L; Nagendrappa, Prakash B; Hilonga, Samson; Naasson, Tuyiringire; Ashuro, Efrata; Kaligirwa, Anita; Sesaazi, Crispin Duncan (Journal of Ethnopharmacology, 2020)
Ethnopharmacological relevance: The increasing national prevalence of diabetes mellitus (DM) and its complications have overstretched the health care system in Tanzania and influenced patients to use herbal medicines as alternative therapeutic strategies. Therefore, an urgent need exists to validate the safety and efficacy of plants used locally. Aim of the study: To identify plants used for the management of DM in Tanzania and analyses their pharmacological, phytochemistry, and safety evidence with a special focus on the mechanism of action. Methods: Researchers searched Medline, web of science, and Scopus for published articles. Also, specialized herbarium documents of Muhimbili Institute of traditional medicine were reviewed. Articles were assessed for relevance, quality, and taxonomical accuracy before being critically reviewed. Results: We identified 62 plant species used locally for DM management. Moringa oleifera Lam. and Cymbopogon citratus (D.C) stapf were the most mentioned. Fifty-four phytochemicals from 13 species had DM activities. These were mainly; polyphenolics, phytosterols, and triterpenoids. Extracts, fractions, and pure compounds from 18 species had in vitro antidiabetic activities of which 14 had α-glucosidase and α-amylase inhibition effects. The most studied -Momordica charantia L. increased; glucose uptake and adiponectin release in 3T3-L1 adipocytes, insulin secretion, insulin receptor substrate-1 (IRS-1), GLUT-4 translocation, and GLP-1 secretion; and inhibited protein tyrosine phosphatase 1 B (PTP1B). Preclinical studies reported 30 species that lower plasma glucose with molecular targets in the liver, skeletal muscles, adipose tissues, pancreases, and stomach. While three species; Aspilia mossambiscensis (Oliv.) Willd, Caesalpinia bonduc (L.) Roxb, and Phyllanthus amarus Schumach. & Thonn. had mild toxicity in animals, 33 had no report of their efficacy in DM management or toxicity. Conclusion: Local communities in Tanzania use herbal medicine for the management of DM. However, only a fraction of such species has scientific evidence. A. mossambiscensis, C. bonduc., and P. amarus had mild toxicity in animals. Together, our findings call for future researches to focus on in vitro, in vivo, and phytochemical investigation of plant species for which their use in DM among the local communities in Tanzania have not been validated.
Keywords: Medicinal plants; Diabetes mellitus; Tanzania; Ethnopharmacology